Multiomics profiling reveals the involvement of protein lactylation in nonhomologous end joining pathway conferring radioresistance in lung adenocarcinoma cell - Jiang He; Tangmin Lai; Zhiying Zhou; Haonan Yang; Zheng Lei; Liu Zhou; Nan Li; Yu He; Siwei Zeng; Erha Munai; Yuanyuan Tan; Miaomiao Wang; et al. (Scientific Reports)
Abstract The novel protein acylation modifications have played a vital role in protein post-translational modifications. However, the functions and effects of the protein acylation modifications in lung adenocarcinoma are still uncertain. Currently, there is still a lack of global identification of acylation modifications in lung adenocarcinoma cells. Therefore, in this study, we detected 10 currently known acylation modifications in lung adenocarcinoma cells by Western blot. We found that the abundance of lysine lactylation (Kla), crotonylation (Kcr) and succinylation (Ksu) is likely higher. Subsequently, we identified the above three modifications together with phosphorylation by global mass spectrometry-based proteomics in lung adenocarcinoma cells. As a result, we got 3110 Kla sites in 1220 lactylated proteins, 16,653 Kcr sites in 4137 crotonylated proteins, 4475 Ksu sites in 1221 succinylated proteins, and 15,254 phosphorylation sites in 4139 phosphorylated proteins. Recent studies have highlighted the role of lactylation modifications in tumor cell resistance to radiation and chemotherapy by affecting homologous recombination. Our subsequent investigations have shown that key factors in the nonhomologous end joining (NHEJ) pathway, such as Ku70 and Ku80, undergo lactylation modifications. Inhibition of lactylation impairs the efficiency of nonhomologous end joining. In conclusion, our results provide a proteome-wide database to study Kla, Kcr and Ksu and phosphorylation in lung adenocarcinoma, and new insights into the role of acylation modification in lung adenocarcinoma.